The Effect of Vernacular Adaptation on Thermal Energy in Semarang Architectural Houses - Sabela, Amalina; Prasetya Sih Handoko, Jarwa; Kholis Idham, Noor (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Semarangan vernacular houses mostly have acceptable thermal performance, primarily related to the roof design and its elements. However, some developments associated with the quality of comfort have already been in progress. We found modifications with an alternative opening in the roof. Testing is needed to determine whether this alteration of a vernacular house with roof modifications is suitable to synchronize to nature and culture for its sustainability. This research aims to assess the quality of the modification for the thermal and energy performance of Semarangan vernacular houses in responding to climate change based on innovation. We utilize an energy audit simulation using the SketchUp software and the Sefaira plugin extension to measure thermal shape and variables. The focused study analyzes the thermal performance of buildings through analysis of the building envelope and building shape from a conceptual model. We discover that vernacular modifications do not reveal any extreme differences. Further research is needed to examine some other types of modifications further. We have to ensure that any modification maintains the quality of the house's performance and even have to increase it.